THE ROLE OF CITY BRANDING ON VISITORS’ REVISIT INTENTION: A STUDY IN MALANG, INDONESIA - Mujihestia, Tita Imamelina (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2018)
The main purpose of this paper is to investigate the influence of city branding on visitors’ revisit intention to Malang city which is well-known as a holiday destination in Indonesia. Study about city branding has been conducted by many researchers before, but study that applied in an enclave city, like Malang, has not been thoroughly examined. In order to make this study result becomes a guideline to design proper marketing strategies, this study will focused on the impact of three city branding attributes that is city image, city authenticity and city uniqueness on visitors’ revisit intention. A quantitative, explanatory approach conducted with visitors’ who chose Malang city as their holiday destination. Results indicate that city branding has a relationship with visitors’ revisit intention and city image plays an important role on the relationship.